Improving replenishment flows using simulation results: A case study - Othmane Benmoussa (Logistics, 2022)
Background: Replenishment process is one of the success factors for a more efficient management of operations and a regained profitability. The application of the principles of lean manufacturing in the field of industrial logistics, where substantial improvements in the replenishment process are necessary, is relevant with the objective of optimising the replenishment flow of raw materials from assembly lines in order to propose and implement robust solutions capable of mitigating or even eliminating all types of waste and maximising the productivity of value-added activities. Methods: To achieve this goal, the paper follows the spirit of the DMAIC (Define, Measure, Analyse, Improve and Control) and 5-Why methods that allow the mapping of internal processes of factory logistics in the particular case of a Wire Harness Automotive Plant. Results: Based on the data collected, as well as on specific analysis methods, simulations are launched to challenge and validate the improvements made to the replenishment process. Conclusions: Several generalisable lessons are learnt regarding replenishment flow management, covering topics such as inventory traceability, in addition to logistics costs and process flow optimisation.
Keywords: 650; inventory; supermarket; line feeding process; DMAIC method; 5-Why; optimisation